Flexible and stretchable mechanoluminescent fiber and fabric. Issue 32 (7th August 2017) - Zhang, Jing; Bao, Luke; Lou, Huiqing; Deng, Jue; Chen, Ao; Hu, Yajie; Zhang, Zhitao; Sun, Xuemei; Peng, Huisheng
Abstract : Flexible and stretchable mechanoluminescent fibers and fabrics have been created to emit light with tunable colors and intensities. Abstract : With the rapid development of wearable devices, rigid and structurally inelastic conventional luminescent devices with heavy energy supply systems can hardly meet the requirements for flexibility and stretchability. Herein, we created a highly stretchable and flexible mechanoluminescent fiber based on transition metal-doped zinc particles and poly(dimethylsiloxane) by a feasible coating method. The resulting composite fiber emitted an intensity-tunable soft light upon stretching and releasing. Moreover, the structure and optical performance were well retained even after 10 000 cycles of stretching and releasing. Furthermore, the color of the composite fiber could also be tuned as green, yellow or orange, and these colors could even be combined in a single fiber. Finally, mechanoluminescent fabrics with various displays were also fabricated by a similar strategy.